GE_GERICHTE P/13773/2018 vom 11. Oktober 2019 - GE Cour de justice (2019)
PERSONNE PROCHE;VICTIME;MORT;BEAUX-PARENTS(CONJOINTS DES PARENTS);ACCIDENT DE LA CIRCULATION | CPP.116.al2; CPP.117.al3; CPP.122.al2; CO.47; CO.49; CPP.121.al1